BATTERY SWAPPING STATIONS FOR ELECTRIC VEHICLES - Chudy, Aleksander (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
Battery swapping is a promising technology when compared with the traditional electric vehicle charging stations. The time spent at a battery swapping station might be similar to the time spent at a filling station. The article presents information on attempts to implement this solution, methods of battery swapping, infrastructure and operation of battery swapping stations, as well as the benefits and key challenges of the battery swapping technology.